6(y+2)=-3(6y-1)+6y

Simple and best practice solution for 6(y+2)=-3(6y-1)+6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(y+2)=-3(6y-1)+6y equation:


Simplifying
6(y + 2) = -3(6y + -1) + 6y

Reorder the terms:
6(2 + y) = -3(6y + -1) + 6y
(2 * 6 + y * 6) = -3(6y + -1) + 6y
(12 + 6y) = -3(6y + -1) + 6y

Reorder the terms:
12 + 6y = -3(-1 + 6y) + 6y
12 + 6y = (-1 * -3 + 6y * -3) + 6y
12 + 6y = (3 + -18y) + 6y

Combine like terms: -18y + 6y = -12y
12 + 6y = 3 + -12y

Solving
12 + 6y = 3 + -12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12y' to each side of the equation.
12 + 6y + 12y = 3 + -12y + 12y

Combine like terms: 6y + 12y = 18y
12 + 18y = 3 + -12y + 12y

Combine like terms: -12y + 12y = 0
12 + 18y = 3 + 0
12 + 18y = 3

Add '-12' to each side of the equation.
12 + -12 + 18y = 3 + -12

Combine like terms: 12 + -12 = 0
0 + 18y = 3 + -12
18y = 3 + -12

Combine like terms: 3 + -12 = -9
18y = -9

Divide each side by '18'.
y = -0.5

Simplifying
y = -0.5

See similar equations:

| 13X=10X-9 | | Y=-x(x-2) | | 3(1)+2(6)=9 | | 3x^2+5x-2y^2=0 | | -x(0)+5y=15 | | -x+0=15 | | 2y-42=4 | | a+4-a(a+4)=0 | | 5h+24=-8(b-6)+6b | | sin(x)=0.5625 | | 1a-4b+2c=0 | | 8p=9 | | 2+19=43 | | sinx=0.5625 | | x(x-8)+2(x-8)=0 | | 5+3y=9 | | Y=5x^2+35 | | z-34.7=68.2 | | 10x+8y+z=100 | | 6x-30=6x+12 | | 5ln(x^2)=4ln(x^3)+6 | | 3x^2-11=37 | | Cry+z=9fory | | y(y-12)+y-12=0 | | 12X+2=76 | | 12X+2=78 | | -4(2x-6)=-6 | | r/5+5=8 | | c/3+3=7 | | -2x+9+4x=-2 | | p/5+7=16 | | 7=x/3+4 |

Equations solver categories